Nutrient removal and recovery from urine using bio-mineral formation processes - Colston, Robert E.; Nair, Ajay; Vale, Peter C. J.; Hassard, Francis; Stephenson, Tom; Soares, Ana (American Chemical Society, 2024)
Harvesting nutrients from waste presents a promising initiative to advance and deliver the circular economy in the water sector while mitigating local shortages of mineral fertilizers worldwide. Urine, a small fraction of municipal wastewater, holds substantial amounts of nitrogen, orthophosphate (PO4–P), and chemical oxygen demand (COD). Separating urine aids targeted nutrient recovery, emissions reduction, and releasing capacity in wastewater treatment plants and taps into overlooked vital nutrients like magnesium (Mg2+) and potassium (K+), essential for plant growth. The ability of selected microorganisms (Brevibacterium antiquum, Bacillus pumilus, Halobacterium salinarum, Idiomarina loihiensis, and Myxococcus xanthus) to remove and recover nutrients from fresh urine through bio-mineral formation of struvite was investigated. The selected microorganisms outcompeted native microbes in open-culture fresh urine, and intact cell counts were 1.3 to 2.3 times larger than in noninoculated controls. PO4–P removal reached 50% after 4 days of incubation and 96% when urine was supplemented with Mg2+. Additionally, soluble COD was reduced by 60%; urea hydrolysis was only < 3% in controls, but it reached 35% in inoculated urine after 10 days. The dominant morphology of recovered precipitates was euhedral and prismatic, identified using energy dispersive spectroscopy and X-ray diffraction as struvite (i.e., bio-struvite), but K+ was also present at 5%. Up to 1 g bio-struvite/L urine was recovered. These results demonstrate the ability of bio-mineral producing microorganisms to successfully grow in urine and recover nutrients such as bio-struvite, that could potentially be used as sustainable fertilizers or chemicals.
Keywords: nutrient recovery; urine treatment; bio-based economy; bio-mineralization; struvite